Utilization of tuna innards as raw material for making fish feed based on organoleptic - Febrina Olivia Akerina; Femsy Kour; Angga Rivanly Kitong; Riki Rikardo Ada; Rendy Simange (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Tuna is one of the abundant potentials in North Halmahera Regency, Tobelo. Tuna fish sold in several markets in the city of Tobelo in the form of intact or have been handled, thus tuna fish waste in the form of innards and gills is not utilized, causing a pungent odor at the sales location. The use of fish waste, one of which is an innards fish can be used as an alternative raw material for making fish feed. The raw material for making fish feed must have good nutritional quality including protein sources. This study aims to find out how to process tuna waste into fish feed and the level of respondent's preference for fish feed made. This research was conducted in October - November 2021. The results show that the average panelist assessment of the texture of artificial fish feed texture ranges from 5.45-6.4, the organoleptic value of artificial fish feed ranges from 5.15 to 5.7, the organoleptic value of artificial fish feed ranges from 5.2 to 5.65.